Structural and mechanical properties of nanostructured TiO2 thin films deposited by RF sputtering - Haseeb, A.S. Md. Abdul; Hasan, M.M.; Masjuki, Haji Hassan (Elsevier, 2010)
This study mainly aims to evaluate the effects of substrate temperatures on the mechanical properties of TiO2 thin films deposited on glass substrates by radio-frequency (RF) magnetron sputtering. All titania films possess anatase structure having a nodular morphology. AES results reveal that Si and Na ions from glass diffuse into TiO2 films at higher substrate temperatures Micro-scratch and wear tests were conducted to evaluate their mechanical and tribological properties The adhesion critical loads of TiO2 films deposited at room temperature, 200 and 300 degrees C are found to be 1.51, 1.54 and 1.08 N. respectively Scratch hardness also Increases from 11.5 to 13 6 GPa with increasing temperature The wear track width decreases with substrate temperature indicating an improved wear resistance at higher temperatures (C) 2010 Elsevier B.V. All rights reserved.